Aspirated [p t k] in sung Spanish: A comparative study of Argentine opera and folk singers’ pronunciation - Guzmán, Mariano Nicolás (2023)
We have proposed to examine the degree of voiceless stops aspiration in Spanish pronounced by Argentines specialized in opera singing (who would be influenced by the phonetic-aesthetic canon) and folkloric singing (without a canonical training). The VOT of these consonants is expected to be higher in the first modality. This would imply that Argentine opera singers foreignize their own pronunciation in order to adjust their interpretations to the classical vocal training requirements.